Nos sertões da Província do Grão-pará: escravidão, engenhos, engenhocas e atividades econômicas no oitocentos (1810-1850) - MEDEIROS, Juliana do Nascimento (Universidade Federal do Pará, 2023)
The main objective of the research is to investigate the agroextractivist properties, especially the sites, the mills and contraptions, using black slavery as a background. As a result of this objective, the structure of ownership of captives will be analyzed, striving to unveil the universe of agricultural properties of which these subjects were fundamental elements. In view of this purpose, I will outline the profile of slaveholders, slaves and properties, revealing the activities carried out in their interiors that are peculiar beforehand, that is, typical of the northern region of this immense country. The research locus is the Amazonian rural world, here called sertão. The hinterland is understood to be the interior regions of the province that bordered the outskirts of Belém, highlighting the localities that made up the Guajarina Zone (Belém, Acará, Capim, Bujaru) and Baixo Tocantins (Cametá, Moju, Abaetetuba and Igarapé-Miri), as it is in these more traditional spaces that agricultural activities have been consolidated. Complex, heterogeneous and plural space. From the properties, it investigated the productive activities and the means by which they were produced, techniques, tools, labor. From the product of the mills and contraptions, the role of the production of sugarcane cachaça and brandy is emphasized; in parallel with activities related to provincial supply and the foreign market. Post-mortem inventories are used as the main source, as a complement to wills, travelers' reports, sources from the overseas historical archive and newspapers.